STUDY OF PUBLIC PERCEPTION ON EFFORTS TOWARDS CONSERVATION OF THE UPPERWATER RESERVATION OF THE KRUENG GEUPU RIVER BASIN, ACEH BESAR - Zakiah, Zakiah; Nelly, Cut (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2024)
This study was conducted to determine the knowledge , attitudes , and actions toward people Mukim Leupung Kr Geupu forests in watershed areas . Leupung in select intentionally ( purposive sampling ) with consideration of the location Mukim located within the watershed region Kr . Geupu . Leupung society is directly related to watershed areas Kr . Geupu . In general, the technique used is simple random sampling with a semi - closed type questions questions , using a confidence level and 95% Confidence Intervals by 5 % . Knowledge related to forest resource conservation issues , 47.5 % of people claim to know Leupung habitation , while the rest , 52.5 % did not know .The percentage of respondents who chose the public as the party most responsible for the damage ( 32.0 % ) and also contained 22.2 % of respondents stated that we all must be responsible for forest destruction .Leupung habitation that people have an understanding , a positive attitude and action in the protection of forests in watershed Kr . Geupu , Aceh Besar is also evidenced by the high community participation in conservation efforts , especially forest Leupung.